2018
DOI: 10.2139/ssrn.3213216
|View full text |Cite
|
Sign up to set email alerts
|

Of Bulls and Bulbs: Aspirations and Perceptions of Rural Youth in Zambia

Abstract: During the last years, policymakers and development-practitioners focused heavily on making farming more attractive for the rural youth in Africa. To reach this goal, different actions are proposed, often emphasizing the need for modern farming and information and communication technologies. These proposed actions are mostly based on anecdotes and prior policy beliefs, but not on empirical evidence since scientists have largely neglected this topic. This paper aims to contribute to a deeper understanding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Studies have used the first approach to explore rural youth's intentions to get involved in farming in Africa (Daum, 2018;Yeboah et al, 2017). Bezu and Holden (2014) and Gella (2013) showed that young women often preferred to look for urban employment compared to their male counterparts, because farming was seen as a male occupation and because inheriting family land proved more difficult for women.…”
Section: Approaches To Analyse Young People's Willingness To Farmmentioning
confidence: 99%
“…Studies have used the first approach to explore rural youth's intentions to get involved in farming in Africa (Daum, 2018;Yeboah et al, 2017). Bezu and Holden (2014) and Gella (2013) showed that young women often preferred to look for urban employment compared to their male counterparts, because farming was seen as a male occupation and because inheriting family land proved more difficult for women.…”
Section: Approaches To Analyse Young People's Willingness To Farmmentioning
confidence: 99%
“…Hedge and Venkattakumar (2015) point out that, to revitalise Indian agriculture, there is a need to bring in profitability through better livelihood options and promoting entrepreneurship, which eventually attract the next generation. Daum (2018) argues that proposed policy briefs on the aspirations and perceptions of young people about farming are not based on empirical evidence. Daum suggests that policymakers and development practitioners pay more attention on the actual aspirations of rural youth to avoid well-intended but misguided policies.…”
Section: Youth and Agriculturementioning
confidence: 99%